On limit theorem for density function and asymptotic expansion in multidimensional case - Lapinskas, R. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Р. Лапинскас. О локальной предельной теореме и асимптотических разложениях в многомерном случае R. Lapinskas. Apie lokalinę ribinę teoremą ir asimptotinius dėstinius daugiamačiu atveju